Pelatihan Public Speaking untuk Meningkatkan Kepercayaan Diri dan Efektivitas Komunikasi Anggota PKK Bojongsoang - Almira Shabrina; Husnita Husnita (Jurnal Pustaka Dianmas, 2026)
Public communication skills are essential in strengthening community-based organizations, including the Family Welfare Empowerment Organization (PKK) as a grassroots platform for women's empowerment. However, PKK members in Bojongsoang still face communication barriers, such as limited self-confidence, public speaking anxiety, and difficulty structuring messages in formal and community forums. This community service program aimed to improve the self-confidence and communication effectiveness of PKK Bojongsoang members through experiential public speaking training. The program involved 43 participants consisting of housewives, Posyandu volunteers, and village officials. The method consisted of need assessment, training design, workshop implementation, performance observation, and post-activity evaluation. The training applied a 30% theory and 70% practice composition through simulations, role play, short speeches, MC practice, peer feedback, and facilitator coaching. Data were analyzed descriptively using frequency and percentage calculations from post-test questionnaires, supported by qualitative interpretation of observation notes and participants' reflections. The findings show that all respondents gave positive responses, with most participants strongly agreeing that the training materials were relevant, clearly delivered, and useful for their communication roles. The activity also produced practical outputs in the form of a public speaking module, participant practice experience, and a follow-up communication group. This program contributes to strengthening the communication capacity and institutional effectiveness of PKK as a community-based organization.